Response rate and nonresponse bias in a questionnaire survey of dentists - Parashos P, Morgan MV, Messer HH (Blackwell Synergy, 2005)
(a) To report on response rate and nonresponse bias of a questionnaire survey of dentists. (b) To make recommendations for future questionnaire survey research in dentistry.